UNILATERAL CONTRACTUAL TERMINATION AND DISPUTE RESOLUTION IN INDONESIA’S CONSTRUCTION PROJECT AND PUBLIC PROCUREMENT - Della Kristina; Tjempaka (Universitas Syiah Kuala, 2026)
This study analyzes the complexities of contractual disputes and termination mechanisms in Indonesia’s construction and public procurement sectors. It identifies unilateral termination and payment delays by government entities as often unlawful acts that leave contractors in a vulnerable bargaining position. The research contrasts litigation options in district and administrative courts with alternative dispute resolution (ADR) methods such as mediation and arbitration, highlighting the varying pathways for enforcement and relief. Study adopts a normative juridical approach, relying on statutory texts, case law, doctrinal discussions, and academic literature. It emphasizes comparative insights where relevant to Indonesian practice and integrates doctrinal analysis with practical considerations from project governance and procurement processes. This `article offers a balanced contractual protection model consisting of three main components: standardization of national construction contract clauses, which regulate the obligation to provide compensation and clarification mechanisms before contract termination is carried out; establishment of a construction contract mediation institution, which is independent, fast, and affordable in terms of cost, to be an effective alternative before resorting to arbitration; and reform of national contractual law, through the adoption of the principles of good faith and equitable remedies. This model is expected to be able to close the gap between law in books and law in action, and ensure that every construction contract is implemented with the principles of fairness, transparency, and shared responsibility.